The engagement party : a novel - Kane, Darby (William Morrow, an imprint of HarperCollinsPublishers, 2023)
Emily Hunt went missing from her affluent liberal arts school on graduation weekend. Her body was found floating in a river, and a quiet loner who most people on campus really didn't know died by suicide. A tenuous link--one text--bound the two dead students together and was enough for law enforcement to close the case. But they got it wrong and now someone is determined to set it right. Twelve years later, college friends gather to celebrate an engagement over a long overdue getaway on a swanky private island in Maine--with only one way in and one way out. Sierra Prescott, invited as a guest and unconnected to past events, is the only person who soon senses not all is what it seems. The tension in the air is ignited when they find a dead man in the trunk of a car with a note: time to tell the truth. And things only get worse. As a torrential storm strands them together, the group's buried stories begin to surface and secrets are bartered. To survive this deadly party, they'll need to stop a killer before they become prey. --Amazon